Antibiotic-treated versus germ-free rodents for microbiota transplantation studies - Lundberg, Randi (Gut Microbes, 2016)
We recently investigated the applicability of antibiotic-treated recipient mice for transfer of different gut microbiota profiles. With this addendum we elaborate on perspectives and limitations of using antibiotics as an alternative to germ-free (GF) technology in microbial transplantation studies, and we speculate on the housing effect. It is possible to transfer host phenotypes via fecal transplantation to antibiotic-treated animals, but problems with reproducibility, baseline values, and antibiotic resistance genes should be considered. GF animals maintained in isolators still seem to be the best controlled models for long-term microbial transplantation, but antibiotic-treated recipients are also commonly utilized. We identify a need for systematic experiments investigating the stability of microbial transplantations by addressing 1) the recipient status as either GF, antibiotic-treated or specific pathogen free and 2) different levels of protected housing systems. In addition, the developmental effect of microbes on host physiological functions should be evaluated in the different scenarios.